Examining the Restriction of Human Rights in Government Regulation in Lieu of Law - Aji, Ahmad Mukri; Nurhalimah, Siti (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The implementation of human rights (HAM) in Indonesia can be restricted while its implementation is violated others’ rights, or contradicted moral considerations, religious values, security, and public order. This limitation is referring to article 28 J of the 1945 Constitution of the Republic of Indonesia (UUD 1945) which has been regulated under the law. Besides, can human rights restrictions also be stipulated through legal products in the form of Government Regulation in Lieu of Law or Perppu? This question is build upon the understanding that Perppu is equated with the law in the hierarchy of statutory regulations. Nevertheless, Perppu that formed in a precarious and a hurry situation must consist of material content restrictions on crucial matters including human rights restriction. The limited contents of the Perppu should become a concern since it must be applied with extra caution and consideration. As a result, the Perppu which was compiled under abnormal conditions should not be justified in regulating human rights restriction.Keywords: Human Right, Restriction of Human Right, Perppu Menelaah Pembatasan Hak Asasi Manusiadalam Peraturan Pemerintah Pengganti Hukum Abstrak:Di Indonesia, Hak asasi manusia (HAM) dapat dibatasi apabila pelaksanaannya menciderai hak asasi orang lain, betentangan dengan pertimbangan moral, nilai-nilai agama, keamanan, dan ketertiban umum. Pembatasan tersebut sesuai pasal 28 J UUD 1945 diatur dalam sebuah undang-undang. Lalu apakah pembatasan HAM juga dapat diatur melalui produk hukum berupa Perppu? Pertanyaan ini didasari oleh pemahaman bahwa Perppu disamakan derajatnya dengan undang-undang dalam hierarki peraturan perundang-undangan. Namun jika diresapi kembali Perppu yang dibentuk dalam keadaan yang genting dan terburu-buru, harus memiliki batasan materi muatan menyangkut hal-hal krusial seperti pembatasan HAM. Tentu saja pebatasan materi muatan Perppu ini patut menjadi perhatian, karena meskipun HAM dapat dibatasi, pembatasan HAM tersebut harus dilakukan dengan sangat hati-hati dan penuh pertimbangan. Sehingga Perppu yang tentu saja disusun dalam kondisi yang tidak normal, sudah sepatutnya tidak dibenarkan untuk mengatur pembatatan HAM.Kata Kunci: Hak Asasi Manusia, Pembatasan Hak Asasi Manusia, Perppu Рассмотрение ограничения прав человекав государственном регулировании вместо закона Аннотация:В Индонезии права человека могут быть ограничены, если их реализация наносит ущерб правам других людей, противоречит моральным соображениям, религиозным ценностям, безопасности и общественному порядку. Это ограничение в соответствии со статьей 28 J Конституции 1945 года регулируется законом. Тогда можно ли регулировать ограничение прав человека с помощью легального продукта в виде Perppu? Этот вопрос основан на понимании того, что Perppu равняется по рангу с законами в иерархии законодательных норм. Однако, если подумать ещё раз, Perppu, который был сформирован в шаткой и поспешной ситуации, должен иметь материальные ограничения в отношении важных вопросов, таких как ограничения прав человека. Конечно, ограничение содержания Perppu заслуживает внимания, потому что, хотя права человека могут быть ограничены, такие ограничения прав человека должны выполняться очень осторожно и с огромным вниманием. Так что Perppu, который, конечно, был составлен в ненормальных условиях, не должен оправданно применяться в регулировании ограничения прав человека.Ключевые слова: Права человека, ограничения прав человека, Perppu